An evaluation of the impact of a policy-level intervention to address psychosocial risks on organisational action in Italy - Di Tecco, Cristina; Jain, Aditya; Valenti, Antonio; Iavicoli, Sergio; Leka, Stavroula (Elsevier, 2017)
Psychosocial hazards have the potential to cause harm to employee health and negatively affect organisational outcomes. Work-related stress is an outcome of exposure to psychosocial risks that has received broad attention at research and policy level in the last decades. Great awareness raising efforts have been made in the European Union, including at the macro policy level, with several differences and approaches across countries. However, evaluation of policy-level interventions to address psychosocial risks is still scarce. This paper focuses on Italy as one of the cases where the policy context on psychosocial risks recently changed with the introduction of the Legislative Decree 81/2008. Using data collected through the European Survey of Enterprises of New and Emerging Risks (ESENER) immediately after (2009) and six years after (2014) the implementation of this new legislation, this paper aims to evaluate the impact of its introduction by exploring differences in the reported level of organisational action as concerns psychosocial risk management. The sample was composed of 2984 respondents corresponding to 1501 highest-ranking managers responsible for health and safety at work in 2009 and 1483 persons who know best about the way safety and health risks are managed at their workplace in 2014. Findings highlighted a decreasing reported concern from the respondents about psychosocial risks over time and an improvement in the management of work-related stress. The paper also highlights the use of large-scale surveys such as ESENER as an important tool in evaluating health and safety management trends over time in European enterprises.